Upaya Peningkatan Hasil Belajar Matematika Menggunakan Model Pembelajaran Kooperatif Tipe STAD pada Materi Bangun Ruang Sisi Datar - Yuliana Priatina (Universitas Indraprasta PGRI, 2018)
The purpose of this research is to increase students mathematics learning outcomes through the STAD type cooperative method. This research was carried out in class VIII A SMP Islam Terpadu At-Taufiq on the material to construct flat side space. The method used is action research or class action. Sample taken were 25 students.